Entrepreneurship Mahasiswa Fakultas Ekonomi - Ismawati, Kun; Pujiani, Dewi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2014)
This research aimed to analyze the point of view about entrepreneurship of students in economic faculty. Respondents of this research were many students in all economic colleges/ universities in Surakarta. This case study analyzed with regression analysis. The research result showed that desire in business and support of family and social life have a positive and significant influence in entrepreneurship decision making of economics students after graduated. Support of family and social life was the most dominant factor in their entrepreneurship decision making. Keywords: economic, regression analysis, entrepreneurship.